Addressing the Needs of Adults and Children with Disabilities through Emergency Preparedness and Organizational Improvisation. Issue 3 (16th November 2016) - Fifolt, Matthew; Wakelee, Jessica; Eldridge‐Auffant, Laurie; Carpenter, Renae; Hites, Lisle
Abstract : The purpose of this qualitative study is to describe the experiences of fifteen organizational leaders and staff members who were responsible for caring for adults and children with disabilities during a 2014 winter storm. This study integrates the literature bases of emergency management and organizational improvisation. In response to this severe unexpected winter weather event, organizational leaders and staff members demonstrated creativity and flexibility in addressing the needs of clients, students, and patients, including adults and children with disabilities. The study concludes with reflections about emergency planning and organizational improvisation, practical implications, and a call to action to learn from these events and provide additional training and resources to individuals who may be in similar situations in the future.